HbA1c: an independent risk factor for dysthyroid optic neuropathy - Wang, Xing; Ye, Huijing; Chen, Rongxin; Yang, Shenglan; Zhang, Te; Xiao, Wei; Yang, Huasheng (Frontiers in Endocrinology, 2023)
• DM and AITD are interconnected linked autoimmune endocrine diseases. The prevalence of combined thyroid dysfunction in patients with T2DM was reported to be 14.0% to 16.0%.• Islet β-cell autoantibodies and function may play roles in thyroid dysfunction and TAO.• Dysthyroid optic neuropathy (DON) patients might have higher HbA1c and fasting plasma glucose.• HbA1c is an independent risk factor for DON in thyroid-associated ophthalmopathy.• Given the inextricable link between thyroid dysfunction and diabetes mellitus, the use of HbA1c as a potential biomarker for DON warrants further investigation.